(3eMGVQGJ GdCOHGA heMGhQGJ GdTYQGA hGdHdZGAs - (3GdMSjf Hf eMeO Hf GdeaVd, CHh GdbGSe GdCUagGfj (B((3Ch GdCUHgGfj(B) (3GdeYQha HGdQGZH,J (B502 (3g` s ((3LdGd GdMSjf Hf GdSjO RjGOI GdSedj s)
(3ChdgG (B:s
(3hHYO, aEf SjOfG CMH Cf CNJGQ dg eeG UfaJ ef fcJ GdCNHGQ, hef Yjhf GdCTYGQ hef ZjQgG ef GdcJH s
(3BNQgG (B:s
(3fgGjI GdMO GdMGOj YTQ bhdg(B: (3CfJ GeQD JOef GdTWQfL ef Sef hEffj jG CHG CjhH egRhod aHYK Edjg HYTQI BdGa OQge hGddg JYGdi CYde HGdUhGH s
(3GfXQ GdLRA GdChd GdQbe (B730 (3COHs
(3QJHg Ydi NeSI hYTQjf MOkGs
(3GdLRA GdChd ef GdMO GdChd Edi fgGjI GdMGOj YTQ HChdgG agQSs
(3hHgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdCOHs